Low-energy high-current electron beam generation in plasma system and beam-plasma interaction - Agafonov, A.V.; Bogachenkov, V.A.; Suleymanov, O.S.; Tarakanov, V.P. (Вопросы атомной науки и техники, 2007)
The review of results of experimental investigations and computer simulations of low-energy high-current electron beam generation in a low-impedance system and dynamics of beam-plasma system are given. The system includes a long plasma-filled diode, an auxiliary thermionic cathode and an explosive emission cathode. The auxiliary cathode is used to generate a low-current, low-voltage electron beam to form long plasma anode by means of a residual gas ionisation in an external longitudinal magnetic field. The high-current low-energy electron beam is generated from the explosive emission cathode embedded in preliminary prepared plasma. Peculiarities of the system are due to: 1) the generation of electron beams with currents exceeding Alfven’s limit; 2) the charge density of the beam close to the plasma density. These peculiarities complicate beam-plasma interaction significantly due to sharp non-uniform distribution of the beam current density, dominant transverse motion of the beam electrons and redistribution of ion-plasma density under the influence of fields. Computer simulation was performed using electromagnetic PIC code KARAT for different geometry’s of the system. Дано огляд результатів експериментальних досліджень і чисельного моделювання генерації низько-енергетичних (з енергією в десятки кілоелектронвольт) потужнострумових (зі струмами в десятки кілоампер) електронних пучків у наповненій плазмою системі з протяжним плазмовим анодом і динаміки всієї системи в цілому. Слабкострумовий низьковольтний пучок від допоміжного катода, що знаходиться у зовнішньому подовжньому магнітному полі, використовується для створення протяжного плазмового анода в залишковому газі. Потужнострумовий електронний пучок формується з вибухоемісійного катода, що стикається зі сформованою плазмою. Особливості системи зв'язані з формуванням потужнострумового пучка з щільністю часток, порівнянної з густиною плазми, і струмом, який перевищує граничний струм Альфвена, що різко ускладнює характер пучково-плазмової взаємодії в процесі транспортування потужнострумового пучка уздовж протяжного плазмового анода за рахунок різко вираженого поперечного руху і неоднорідного розподілу струму пучка. Дан обзор результатов экспериментальных исследований и численного моделирования генерации низкоэнергетических (с энергией в десятки килоэлектронвольт) сильноточных (с токами в десятки килоампер) электронных пучков в плазмонаполненной системе с протяженным плазменным анодом и динамики всей системы в целом. Слаботочный низковольтный пучок от вспомогательного катода, находящегося во внешнем продольном магнитном поле, используется для создания протяженного плазменного анода в остаточном газе. Сильноточный электронный пучок формируется со взрывоэмиссионного катода, соприкасающегося со сформированной плазмой. Особенности системы связаны с формированием сильноточного пучка с плотностью частиц, сравнимой с плотностью плазмы, и током, превышающим предельный ток Альфвена, что резко усложняет характер пучково-плазменного взаимодействия в процессе транспортировки сильноточного пучка вдоль протяженного плазменного анода за счет резко выраженного поперечного движения и неоднородного распределения тока пучка.